Feminisme sebagai Diskursus Pandangan Hidup - Abdullah Muslich Rizal Maulana (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
In perspective of Postmodern West, thought discourses always colored by relativism, equality, nihilism, and reconstruction. This discourses of thought, cannot be separated from the profane Western worldview, which formed during the several hundred years of experience theological, sociological, and historical of West. Nowadays –Postmodern- worldview became the foundation for providing responses to the phenomenon that exist in the West, including feminism and gender. Islam, such as din and ideology is conceptually also obligated to set up the concept of worldview projected by texts in the form of the Quran and al-Hadith. Both this primary source of Islam derived concepts about God, Nature, Science, Mind, Soul, and so forth as a spectrum set of Muslims viewpoints in doing things. Related here, Islamic worldview is necessary to observe, analyze, to the stage critiquing feminism and gender discourse that is a product of western Worldview. Islamic Worldview demanded to review and response proportionally to discourses of western Worldview which has difference with Islam conceptually.